Grandiose narcissists and decision making: Impulsive, overconfident, and skeptical of experts–but seldom in doubt. (1st January 2021) - O'Reilly, Charles A.; Hall, Nicholas
Abstract: A substantial body of research has documented that grandiose narcissists are characterized by high self-esteem, a sense of personal superiority and entitlement, overconfidence, a willingness to exploit others for self-gain, and hostility and aggression when challenged. We report two studies ( N = 452) that explore how these dispositions affect their decision making. We show that grandiose narcissists' overconfidence, impulsivity, and a willingness to ignore expert advice results in a higher likelihood of making a bad decision. In addition, after getting the wrong answer, grandiose narcissists are more likely to blame others and remain self-confident in their judgment. Highlights: Grandiose narcissists are overconfident and often rely on their own intuition to make decisions. This can lead them to make less accurate decisions. They remain confident in their decisions and externalize blame. They also often assume leadership positions in organizations. These tendencies can put the organizations they lead at risk.